Pedagoška praksa kot motivacija za ustvarjalno likovnopedagoško delo bodočih likovnih pedagogov - Herzog, Jerneja; Duh, Matjaž; Batič, Janja (Revija za elementarno izobraževanje, 2009)
The teaching practice as motivation for future art teachers. At the Faculty of Education in Maribor we have been using didactics lectures and practical lessons as a way of motivating future art educators. Teachers who are not motivated for art education themselves will hardly be able to motivate their pupils or students. Teaching in the classroom is of key importance and is a part of the studies in the third and fourth years of university, performed at elementary and secondary schools. As a part of their practical training, students get acquainted with a school's everyday environment, try out theories in practice, interact with students and teachers and continue to gain experience. In fact, it is the latter that comes closest to the pedagogical part of their study: where students are motivated to further develop their own art education practice. But it can also have a directly opposite effect. During the 2008/2009 study year, we interviewed students who were in the third and fourth years of art education (n = 34) , after they had completed their practice in classroom teaching. We wanted to find out how these students viewed practical teaching, the experience they had gained etc. We established that students predominantly estimated their experiences in teaching as positive, yet there are still some areas that need improvement.